Antibacterial potency of fresh extract leaves of jamaican cherry (Muntingia calabura L.) in Inhibiting the growth of Shigella dysenteriae. - Ikel Fitri Yanis; Feskaharny Alamsjah; Anthoni Agustien; Tesri Maideliza (Universitas Andalas, 2020)
Research on the antibacterial potency of fresh extract from leaves of Jamaican cherry (Muntingia calabura L.) in inhibiting the growth of Shigella dysenteriae had been conducted in the Microbiology Laboratory, Department of Biology, Faculty of Mathematics and Natural Sciences, Andalas University. The study aimed to determine the potential of fresh extract from Jamaican cherry leaves in inhibiting the growth of S. dysenteriae and to determine its Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) against S. dysenteriae. The results showed that the fresh extract of Jamaican cherry leaves was potent as an antimicrobial agent against pathogenic bacteria S. dysenteriae. It was shown through 12 - 14 mm diameter of inhibition zone which was classified as strong inhibition. The MIC was measured at 3.125% while MBC was undetermined. According to these findings, it can be concluded that the fresh extract from Jamaican cherry leaves was potent to inhibit the growth of S.dysentriae at 3.125% concentration, yet unable to kill it.